Cyclodextrins as Modulators of Gut Microbiota: Pharmaceutical Applications and Impact on Intestinal Health - Renata Maria Varut; Mircea Sorin Ciolofan; Maria Elena Veronica; Kristina Radivojević; Diana Maria Trasca; Cristina Popescu; Oana Diaconu; Cristina Elena Singer (Pharmaceutics)
Background/Objectives: Cyclodextrins (CDs) have garnered increasing attention in pharmaceutical research due to their ability to enhance drug solubility, bioavailability, and therapeutic efficacy. Meanwhile, the gut microbiota, a key regulator of human health, has emerged as an important target in evaluating the safety and broader implications of pharmaceutical excipients. This review aims to synthesize current knowledge regarding the effects of CDs on the composition and function of the gut microbiota. Methods: A literature search following PRISMA guidelines was conducted in PubMed, ScienceDirect, and Google Scholar to identify studies on cyclodextrins and their interactions with gut microbiota. Results: Cyclodextrins, particularly α-, β-, and γ-CDs, demonstrated the capacity to modulate gut microbiota composition, promoting the growth of beneficial bacteria such as Bifidobacterium and Akkermansia. Supplementation with CDs was also associated with an increased production of short-chain fatty acids (SCFAs), which are essential for maintaining intestinal homeostasis and metabolic health. Moreover, CDs exhibited potential in lowering lipid levels and improving postprandial glycemic control without enhancing insulin secretion. Although generally recognized as safe, the toxicological profile of CDs varies depending on their type, dosage, and route of administration. Conclusions: Cyclodextrins hold considerable promise not only as pharmaceutical excipients but also as modulators of gut microbial communities, suggesting a dual therapeutic and prebiotic role. Future studies integrating metagenomic and metabolomic approaches are necessary to further elucidate the molecular mechanisms underlying CD–microbiota interactions and to optimize their application in enhancing drug delivery efficiency and promoting intestinal health.